R MODEL PEMBELAJARAN MENGGUNAKAN PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) BERBANTUAN QUIZIZZ UNTUK MENINGKATKAN PEMECAHAN MASALAH - rahmawati rahmawati (Universitas Tamansiswa Palembang, 2021)
This study aims to see the improvement of students' mathematical problem solving skills using a learning model using Numbered Head Together (NHT) cooperative learning assisted by Quizizz to improve problem solving. The NHT learning method is a learning method that uses cooperation among students to achieve learning objectives. The subject of the research is the seventh grade students of SMK N 1 Air Kumbang in the academic year 2020-2021. This method is Quasi-Experimental. There are two types of research data, quantitative and qualitative data. The data were analyzed using descriptive analysis and obtained calculations. It was found that students who received learning with NHT (Numbered Head Together) cooperative learning assisted by Quizizz get a higher post test score.